All Days 1994
DOI: 10.2118/28842-ms
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Gas Saturation Buildup During Depressurisation of a North Sea Oil Reservoir

Abstract: When a waterflooded oil reservoir is to be depressurised, it is important to predict the production of solution gas from the by-passed and trapped oil. To quantify the gas saturation build-up and the relation between gas mobility and gas saturation, we have carried out a large number of experiments on core samples. These pressure-depletion experiments, which were conducted at various depletion rates and with both model fluids and actual reservoir fluids, began from one of two starting conditions: reservoir roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 1 publication
5
44
0
Order By: Relevance
“…A mathematical model was developed to describe this behaviour (2), which was allo consistent with the results from high pressure core experiments performed by Kortekaas and van Poelgeest (3,4), and by Scherpenisse et al (5) . Subsequens visual experiments using a two component hydrocarbon mixture in a glass micromodel (6) suggested that both rock wettability and the oil spreading coefficient could substantially influenee the value of the critical gas saturation .…”
Section: Introductionsupporting
confidence: 64%
“…A mathematical model was developed to describe this behaviour (2), which was allo consistent with the results from high pressure core experiments performed by Kortekaas and van Poelgeest (3,4), and by Scherpenisse et al (5) . Subsequens visual experiments using a two component hydrocarbon mixture in a glass micromodel (6) suggested that both rock wettability and the oil spreading coefficient could substantially influenee the value of the critical gas saturation .…”
Section: Introductionsupporting
confidence: 64%
“…Pore-network simulations conducted by McDougal and Sorbie (1999) and Wang and Mohanty (1999) in the related topic of gas condensation, showed that S gc decreases as the hydrostatic pressure gradient increases, a trend also anticipated in Scherpenisse et al (1994). In a parallel study ), we h a ve analyzed the e ect of gravity and/or viscous forces on S gc , a n d developed scaling laws for the dependence of S gc on f qf and on two dimensionless parameters, the Bond and capillary numbers, de ned respectively as B = gk and Ca= q (2) Here denotes the density di erence between liquid and gas, k is permeability, the liquid-gas interfacial tension, q the liquid ow rate and the liquid viscosity.…”
Section: Introductionmentioning
confidence: 72%
“…T h e p o wer-law scaling with exponent 1, predicted by the theory in this range, is well supported by the data. Finally, a comparison of the evolution of the gas saturation, S g , as a function of the dimensionless pressure P Dl = P=P b , using the full solution for the Berea sandstone experiments of Scherpenisse et al (1994) is presented in Fig. 14.…”
Section: Comparison With Experiments a Constant Pressure Decline mentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that as soon as the critical gas saturation is reached, gas becomes mobile, migrates to the top of the structure and is produced resulting in fast pressure depletion and low recovery factors accordingly (e.g. Kortekaas & van Poolgeest 1991, Scherpenisse et al 1994. However, if the liquid mobility is increased compared with the gas mobility, higher recovery factors can be expected (Firoozabadi & Aronson 1999).…”
Section: Recovery Mechanismmentioning
confidence: 99%